The effect of distastefulness and conspicuous coloration on the post-attack rejection behaviour of predators and survival of prey. (23rd August 2016) - Halpin, Christina G.; Rowe, Candy
Abstract: Aposematic insects use bright colours and/or distinct markings to advertise their toxins to potential predators. When toxins are bitter-tasting and detectable upon attack, birds are able to use taste when making decisions about whether or not to eat defended prey. Taste-rejection behaviour, when birds taste but do not ingest a prey item, is often assumed to increase the survival of defended prey, yet few empirical studies have investigated the post-attack survival rates of live defended insects. We used naïve domestic chicks ( Gallus gallus domesticus ) foraging on live waxmoth larvae ( Galleria mellonella ) in a laboratory setting, where conspicuousness and distastefulness could be controlled and manipulated to investigate the effects of taste-rejection behaviour, as well as the associated handling behaviour, on post-attack survival of prey. We found that being distasteful increased the probability of being rejected by naïve chicks, and taste-rejection behaviour tended to be more frequent when distasteful prey were conspicuous compared with when they were cryptic. Conspicuous coloration also appeared to affect predators' assessment of prey distastefulness, with past experience strongly influencing the probability that conspicuous (but not cryptic) prey were rejected. However, in contrast to previous findings, there was no evidence that either distastefulness or conspicuousness altered how predators handled the prey before making a decision about whether or not to eat it, in any way that enhanced prey survival post-attack. Therefore, taste-rejection behaviour appears to be a useful measure of prey survival. Our results provide novel insights into the potential importance of signal conspicuousness for prey populations with variable defences, and highlight the need to consider the role of taste-rejection behaviour in mimicry dynamics.